PERBAIKAN KUALITAS LAYANAN UNTUK MENINGKATKAN KEPUASAN DAN LOYALITAS KONSUMEN DENGAN METODE SERVQUAL DAN STRUCTURAL EQUATION MODELING (SEM) DI MIROTA, SURABAYA - Sharleen Ekaputri Limantoro; Rosita Meitha Surjani; Mochammad Arbi Hadiyat (CALYPTRA, 2013)
Retail is a business opportunity that is widely used by entrepreneurs so that business competition among retail businesses is tight. Therefore, retailers need to do efforts in order to survive. In this research the retail discussed is Mirota. Mirota is a retail store that sells a various products of typical Indonesian culture. Everyday, Mirota is visited by many customers from domestic and foreign countries travelling to Surabaya so that its existing problems are often consumer complaints. Based on existing problems, Mirota needs improving the service quality. The improvement of service quality to increase customer satisfaction and consumer loyalty was conducted by using SERVQUAL method and Structural Equation Modeling (SEM). The purpose of this research is to measure and evaluate the causes of service quality discrepancies, to know the relationship between service quality, customer satisfaction, and customer loyalty, and to propose proposal improvements. The gained results from this research was a gap 5 on quality of service at Mirota. The gap was caused by the gaps 1, 2, and 4. Quadrant analysis performed to determine the weaknesses of the company were based on the comparison of the level of expectations and consumer perceptions. The results of measurements of the relationship quality of service, customer satisfaction and customer loyalty were found that there was the influence of service quality on customer satisfaction by 0.499, the effect of customer satisfaction on customer loyalty at 0.66, but there was no significant effect of service quality on customer loyalty. The results of the analysis slices quadrant IV and the close relationship between the model used as a reference in determining improvement using by Quality Function Deployment (QFD). From the QFD results, the main improvement was done by looking at the importance of how the value of more than 245.4. Improvements are doing market research, providing parking directions and updating parking system with the valley system, giving goods directions and arranging the goods.